Vivendo em comunidade: formas de sociabilidade e sentimento de pertença no catolicismo contemporâneo - Silva, Patrick Cézar da (2012)
This paper will discuss the Community Sweet Mother of God as a part of this particular phenomenon in Contemporary Catholicism, called the New Communities or Communities of Life and Alliance (CVA), whose objective is to analyze how the belong is constructed and /or reconstructed from the perception of the main forms of sociability developed in the community, and how members interpret the experience of the community approach. For this, we intend to discuss how the Communities of Life and Alliance, are presented as a proposal for the development of a religious life that is able to contribute to the maintenance and strengthening of religious belonging within Catholicism, with the context of modernity.